Integrasi Pendidikan Karakter dan Multikultural di Perguruan Tinggi: Membangun Generasi Mahasiswa yang Toleran dan Beretika - Mohammad Rudiyanto; Abi Muhlisin; Sabar Narimo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to examine the integration of character and multicultural education in higher education, focusing on the development of tolerance and ethical attitudes among students. In the midst of cultural diversity in Indonesia, it is important for universities to implement education that not only pays attention to academic aspects, but also shapes the character of students to become ethical individuals who are able to coexist in a plural society. Through a descriptive qualitative approach with a case study at Madura University, this research explores various programmes, policies, and courses that combine the two concepts. The research findings show that the integration of character and multicultural education on campus can strengthen students' understanding of cultural diversity, as well as shape attitudes of tolerance, empathy and openness. However, the implementation of this integration faces challenges, such as resistance from some lecturers and students and limited resources. This study recommends the development of a more inclusive curriculum and policies that support the synergy between character and multicultural education. Further research is needed to evaluate the long-term impact of this integration on character building and students' readiness for the world of work.